Determinação do potencial agroenergético na região da bacia do São Francisco Verdadeiro, utilizando ferramentas de geoprocessamento - Mari Junior, Alvaro (2014)
The overall population growth coupled with technological advances means that there is a growing demand for energy, which results in the search for sources to meet this need . To seek less impactful ways of obtaining energy , the renewable ones began to take space in the research lines related to the generation of this important input , and among such energy sources is vegetable oil that can be extracted from oilseeds . However , when trying to view the energy potential of wind energy , the limitations on the area for cultivation , as tool to aid preparation of planting plans of such plants arises geoprocessing becomes feasible to allow an analysis of various physical characteristics and climate , the elaborate work used a new methodology grounded in geoprocessing , and it found a potential of up to 137,436 tonnes of vegetable oil using canola crop that was growing in that region studied showed better adaptability , the other crops had lower potential , respectively and found the maximum potential production of vegetable oil in the values of 1,304 , 9,974 and 55,464 tonnes for the cultivation of Sunflower, Soybean and Cotton respectively. The methodology presented costs for obtaining the results , however it presented a disability by failing to accurately define the regional water system , thus necessitating future studies aimed at improving the same